Developmental trajectories of health‐promoting behaviours among pregnant women: A longitudinal study. Issue 1 (14th January 2022) - Yu, Pengli; Zhou, Lixue; Meng, Fei; Xu, Yanhong; Jiang, Yunxia; Zhou, Yunping
Abstract: Aims and objectives: The aim of this study is to estimate differences in health‐promoting behaviour levels throughout the pregnancy trimesters, to identify distinct patterns of health‐promoting behaviour trajectories during pregnancy and to evaluate predictors of these trajectory group memberships. Background: Promoting healthy lifestyle behaviours during pregnancy could decrease devastating outcomes for the mother and foetus. However, there is currently limited insight into the dynamics of health‐promoting behaviours during pregnancy. Design: An observational longitudinal study. Methods: 158 pregnant women were recruited from June 2020 to June 2021 in Qingdao, China. The Health‐Promoting Lifestyle Profile was used to assess health‐promoting behaviours. Latent growth model was performed to compare health‐promoting behaviours at different time points. Group‐based trajectory model was applied to identify health‐promoting behaviour trajectories. Multinomial logistic regression was adopted to determine the predictors of trajectory group memberships. We used the STROBE checklist to report this study. Results: The entire sample of pregnant women experienced a significant increase in health‐promoting behaviours during pregnancy. Three trajectories were identified including a 'low‐increase behaviour trajectory (20.1% of sample)', a 'moderate‐increase behaviour trajectory (58.0% of sample)' and a 'stable then increased behaviour trajectory (21.9% of sample)'. Low maternal sense of coherence, lack of pre‐pregnancy exercise habit, artificial insemination and low monthly family income were significantly associated with the low‐increase behaviour trajectory. High self‐efficacy and pre‐pregnancy exercise habit were significantly associated with the stable then increased behaviour trajectory. Conclusions: Pregnant women exhibit different health‐promoting behaviours throughout the pregnancy trimesters. Meanwhile, three trajectories were identified among pregnant women. Thus, more attentions should be paid on early identification and targeted intervention in a future study. Relevance of clinical practice: Healthcare providers should pay closer and earlier attention to identify women in the low‐increase trajectory subgroup at the outset of pregnancy. Similarly, increased efforts should be made to improve maternal self‐efficacy and develop good pre‐pregnancy exercise habit in future study.